2016
DOI: 10.1080/15592294.2016.1146852
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alteration of imprinted genes during neural differentiation of germline-derived pluripotent stem cells

Abstract: Spermatogonial stem cells (SSCs), which are unipotent stem cells in the testes that give rise to sperm, can be converted into germline-derived pluripotent stem (gPS) by self-induction. The androgenetic imprinting pattern of SSCs is maintained even after their reprogramming into gPS cells. In this study, we used an in vitro neural differentiation model to investigate whether the imprinting patterns are maintained or altered during differentiation. The androgenetic patterns of H19, Snrpn, and Mest were maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…DNA methylation status of imprinted genes may be maintained or altered during the generation of pluripotent stem cells [33]. We previously reported that the androgenetic imprinting status of H19 and Mest is maintained after reprogramming of mouse spermatogonial stem cells into germline-derived pluripotent stem cells [34]. In the present study, we confirmed that our PgHiPSCs are similar to parthenogenetic HiPSCs derived from ovarian teratoma primary fibroblasts (GM01304 and GM01306) [31].…”
Section: Discussionsupporting
confidence: 86%
“…DNA methylation status of imprinted genes may be maintained or altered during the generation of pluripotent stem cells [33]. We previously reported that the androgenetic imprinting status of H19 and Mest is maintained after reprogramming of mouse spermatogonial stem cells into germline-derived pluripotent stem cells [34]. In the present study, we confirmed that our PgHiPSCs are similar to parthenogenetic HiPSCs derived from ovarian teratoma primary fibroblasts (GM01304 and GM01306) [31].…”
Section: Discussionsupporting
confidence: 86%
“…Gene set enrichment analysis revealed significant downregulation of several biological processes in the null EBs at day 5, with multicellular organismal development (MOD) and cell surface receptor linked signal transduction (CSRLST) among the most affected ( Figure 3 B). In the MOD category, 15 of 50 genes were among the core enrichment group in the null EBs, including Pax5, Msx2, Gli1, Spry2 , and Mest , which are all important for early development or ESC differentiation ( Lee et al., 2016 , Szabo et al., 2009 , Tefft et al., 1999 , Urbanek et al., 1997 , Wu et al., 2015 ) ( Figure S4 B and Table S2 ). In the CSRLST category, 7 of 30 genes were in the core enrichment group, including Grb10 , the most downregulated gene in the null EBs ( Figure S4 C and Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…These RNA-binding protein complexes have been detected at promoters of NANOG, SOX2 (promoter of lineage plasticity in NEPC [ 28 ]), and FGF4 [ 153 ]. H19 has also been identified in neural differentiation of pluripotent stem cells [ 154 ] but with unknown mechanisms. With such an elevated level of expression in the clinical cohorts (∼30- to 40-fold and ∼20- to 30-fold in VPC/WCM for LINC00617 and H19, respectively), these lncRNA could be responsible for maintaining the neuronal component of NEPC through epigenetic regulation.…”
Section: Discussionmentioning
confidence: 99%